Professional Readaptation in the Context of Individual Social Mobility - Panov, Nikita (Psychological Prospects Journal, 2018)
The research paper explains the significance of the social factor in the range of problems of professional psychology. The change in the mechanisms of social stratification in the postmodern society has led to the intensification of social mobility. In these conditions, professional activity is the main means and way of self-realization of personality. Labour mobility is described as a set of professional changes and displacements that perform various functions. Specific subjective motivations and internal factors of the profession change are demonstrated. The specific features of social mobility that characterize post-soviet and modern Ukraine are analyzed: regressive transformations of the economy, unbalanced labour market, significant volumes of labour migration, gender inequality, etc. It has been shown that education and competence are inadequate as a social lift, both because of numerous problems in the educational system and due to the impact of social inequality that occurs at the beginning of the professional path. Crisis social phenomena play a dual role in the life of a specialist: they either stimulate subjective activity and constructive development, or cause manifestations of professional deadaptation. In this case, the action of external factors is refracted through a complex set of personality traits that make up the adaptive potential of an individual. The contradiction is revealed regarding the role of professional identity as a criterion for effective professionalization of an individual. In today’s transformational globalized world, it is a broad and flexible social identity that serves as a resource for the adaptation potential of a specialist. The terminological field, which reflects the peculiarities of professionalism in the 21st century, is outlined as a set of competencies that helps in employment and allows succeeding in different life spheres with stable variability of the environment.